한약재 함유 헤어토닉 및 식품이 C57BL/6 마우스의 탈모 모델에서 모발성장에 미치는 영향 - 최혜민; Hye Min Choi; 황수정; Su Jung Hwang; 이진상; Jin Sang Lee; 도은주; Eun Ju Do; 김무영; Mu Young Kim; 김미려; Mi Ryeo Kim (大韓本草學會誌, 2011)
Objective: This study was carried out to investigate effect of korean medicinal herbs-included hair tonic (MHT) and food (MF) on hair growth in an alopecia model of C57BL/6 mice. Methods: Six-weeks old mice were given laboratory rodent chow diet for 1 week. Then, we used a depilatory for hair removal on mice. The next day, mice were randomized and separated in 3 groups of 6 mice; normal group (N, vehicle epidermal application+normal diet-treated group), positive control group (C, 3% minoxidil sulfate epidermal application+normal diet-treated group), and the treatment group (T, HT epidermal application+ MF diet-treated group). The hair regrowth was determined by photograph, which was taken at 7, 14 and 21 days. And scoring indices, hair density and hair thickness, were evaluated by Folliscope at same day. In addition, the hair regrowth was analyzed insulin-like growth factor (IGF-1) in the dorsal skin of mice. Results: As a result, not only external appearance but also hair density and hair thickness on dorsal skin were increased more in C, T groups than in N group at 21 days with mixed treatment. Therefore, distinct regrowth pattern is appeared by treatment of herbal tonic and natural food for 21 days. Also, the expressions of IGF-1 on dorsal skin were higher in C, T groups than in N group. Conclusion: These results suggested that this herbal hair tonic and natural food has hair growth promoting activities and may be useful for treatment of bald or alopecia.